2011
DOI: 10.1063/1.3608137
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic endothelial cell culture model to replicate disturbed flow conditions seen in atherosclerosis susceptible regions

Abstract: Atherosclerotic lesions occur non-randomly at vascular niches in bends and bifurcations where fluid flow can be characterized as "disturbed" (low shear stress with both forward and retrograde flow). Endothelial cells (ECs) at these locations experience significantly lower average shear stress without change in the levels of pressure or strain, which affects the local balance in mechanical stresses. Common in vitro models of atherosclerosis focus primarily on shear stress without accounting for pressure and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…72 By exposing HAECs to these types of flow, the authors concluded that in the absence of pro-inflammatory stimulation, PECAM-1, VCAM-1, and ICAM-1 were not significantly upregulated by flow condition. Cells cultured under disturbed flow exhibited round shape and random orientation.…”
Section: Flow-based In Vitro Models and Cams Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 By exposing HAECs to these types of flow, the authors concluded that in the absence of pro-inflammatory stimulation, PECAM-1, VCAM-1, and ICAM-1 were not significantly upregulated by flow condition. Cells cultured under disturbed flow exhibited round shape and random orientation.…”
Section: Flow-based In Vitro Models and Cams Expressionmentioning
confidence: 99%
“…Disturbed and non-laminar flow below healthy physiological levels of shear stress (10-70 dyn/cm 2 ) can cause EC phenotype changes resulting in pro-inflammatory endothelium. [70][71][72] Here, we review in vitro models developed for determining the role of disturbed flow patterns on CAM expression and leukocyte recruitment, and conclude with the testing of targeted particles against CAMs in such models.…”
Section: Flow-based In Vitro Models and Cams Expressionmentioning
confidence: 99%
“…8 Endothelial cells form an inside lining of blood vessels and are important participants in plaque formation. Function of these cells may be affected by the disturbed flow patterns associated with partially occluded blood vessels.…”
Section: Microdevices For Cell Cultivation and Analysismentioning
confidence: 99%
“…1,2 This special topics section provides a sample of the types of microsystems being developed for cell analysis and manipulation. The research directions covered in this thematic section include sorting of mammalian cells, 3,4 pairing of mammalian cells, 5 sorting of viral particles, 6 concentration of bacteria, 7 cultivation of cells in microfluidic devices, 8,9 on-chip monitoring of cell function, 10 and on-chip flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…This type of 3D complexity is essential to accurately mimic the in vivo flow patterns which are fundamental in the mechanism of thrombosis. 14,25,26 Three-dimensional printing has the potential to revolutionize the field of microfluidics by allowing to overcome the limitations posed by conventional 2D wafer-based microfabrication techniques. 22 Furthermore, it allows the fabrication of fully 3D structures, which closely mimic the natural shape of complex human tissue structures and could, therefore, also be useful in replicating the architecture of human blood vessels.…”
Section: Introductionmentioning
confidence: 99%